2020
DOI: 10.3390/pharmaceutics12070635
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Alanine and Glutathione as Targeting Ligands of Nanoparticles Enhances Cargo Delivery into the Cells of the Neurovascular Unit

Abstract: Inefficient drug delivery across the blood–brain barrier (BBB) and into target cells in the brain hinders the treatment of neurological diseases. One strategy to increase the brain penetration of drugs is to use vesicular nanoparticles functionalized with multiple ligands of BBB transporters as vehicles. Once within the brain, however, drugs must also be able to reach their therapeutic targets in the different cell types. It is, therefore, favorable if such nanocarriers are designed that can deliver th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 71 publications
8
21
0
Order By: Relevance
“…The permeability of the model for both SF and EBA was very low (0.52 × 10 −6 cm/s and 0.06 × 10 −6 cm/s), reflecting a tight barrier ( Figure 8 ). These P app values for permeability marker molecules are in accordance with our previous results [ 7 , 25 , 35 ]. The penetrations of all tested RhB-labeled SLNs were several times higher than that of the marker molecules ( Figure 8 ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The permeability of the model for both SF and EBA was very low (0.52 × 10 −6 cm/s and 0.06 × 10 −6 cm/s), reflecting a tight barrier ( Figure 8 ). These P app values for permeability marker molecules are in accordance with our previous results [ 7 , 25 , 35 ]. The penetrations of all tested RhB-labeled SLNs were several times higher than that of the marker molecules ( Figure 8 ).…”
Section: Resultssupporting
confidence: 93%
“…In general, cationic nanoparticles are supposed to be better internalized than neutral and negatively charged NPs, but recent comparative studies prove that neutral or negatively charged NPs are more efficient for drug delivery across the blood–brain barrier [ 49 ]. In our previous studies, we successfully used negatively charged NPs functionalized with ligands of brain endothelial transporters for targeting the blood–brain barrier [ 15 , 35 , 50 ]. The data of the six-month stability experiments also support that the zeta potential of our formulations does not affect significantly the size or aggregation of the SLNs.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the analysis of the percentage of the cellular translocation demonstrated that the PBCA-NP can pass through the hCMEC/D3 cell monolayer. These translocations can be further determined as BBB transport kinetics and represented in the apparent BBB permeability coefficient (P app ) ( Mészáros et al, 2018 ; Porkoláb et al, 2020 ). However, the insert membrane with 8 µm pore size may be too large and this may be the limitation of the system.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we systematically tested vesicular NPs made from non-ionic surfactants (niosomes), labeled with a single or dual combination of three different ligands targeting nutrient transporters of the BBB [12]. We demonstrated that the combination of alanine and glutathione significantly increased the uptake and permeability of the NPs across the in vitro model of the BBB compared to the non-targeted or single-targeted NPs [12,13]. Dual-targeting of NPs also elevated the brain penetration of the encapsulated cargo in mice [12].…”
Section: Introductionmentioning
confidence: 99%
“…Dual-targeting of NPs also elevated the brain penetration of the encapsulated cargo in mice [12]. Furthermore, the delivery of a large protein cargo was enhanced by alanine-glutathione dual-targeted NPs not only into cultured brain endothelial cells but also into pericytes, astrocytes and neurons [13]. In our most recent work, we investigated the initial docking step between the targeting ligand glutathione and the cell membrane of living brain endothelial cells.…”
Section: Introductionmentioning
confidence: 99%